2021
DOI: 10.1051/0004-6361/202141103
|View full text |Cite
|
Sign up to set email alerts
|

The GRAVITY young stellar object survey

Abstract: Context. The formation and evolution of planetary systems impact the evolution of the primordial accretion disk in its dust and gas content. HD 141569 is a peculiar object in this context as it is the only known pre-main sequence star characterized by a hybrid disk. Observations with 8 m class telescopes probed the outer-disk structure showing a complex system of multiple rings and outer spirals. Furthermore, interferometric observations attempted to characterize its inner 5 au region, but derived limited cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…From Castro et al (2014), we can use a typical line width of 0.03 μm for the 3.3 μm feature to estimate the total flux density upper limit at 83 mJy. However, we note that this assumes the emitting region was captured within the 0 6 wide slit used by Geers et al (2007). Second, the PAH lines at 6.26, 7.98, and 11.28 μm were well-measured in Spitzer spectra (Sloan et al 2005), with flux ratios reported as F 6.2 /F 7.9 = 0.4 and F 11.2 /F 7.9 = 0.04.…”
Section: Possible Detection Of Thermal Pah Emissionmentioning
confidence: 86%
See 1 more Smart Citation
“…From Castro et al (2014), we can use a typical line width of 0.03 μm for the 3.3 μm feature to estimate the total flux density upper limit at 83 mJy. However, we note that this assumes the emitting region was captured within the 0 6 wide slit used by Geers et al (2007). Second, the PAH lines at 6.26, 7.98, and 11.28 μm were well-measured in Spitzer spectra (Sloan et al 2005), with flux ratios reported as F 6.2 /F 7.9 = 0.4 and F 11.2 /F 7.9 = 0.04.…”
Section: Possible Detection Of Thermal Pah Emissionmentioning
confidence: 86%
“…We can compare this PAH emission to what might be expected from the disk. First, Geers et al (2007) found a spectroscopic upper limit to the flux density from 3.3 μm PAH emission of 6.9 × 10 −16 W m −2 for the HD 141569A system. From Castro et al (2014), we can use a typical line width of 0.03 μm for the 3.3 μm feature to estimate the total flux density upper limit at 83 mJy.…”
Section: Possible Detection Of Thermal Pah Emissionmentioning
confidence: 99%